Sexually transmitted proctitis - Nadal,Sidney Roberto (2012)
Proctitis caused by sexually transmitted agents is usually taken for inflammatory bowel diseases, because of similar complaints, such as pain, bleeding and mucopurulent discharge, as well as the histopathology. Thus, its treatment is postponed and, sometimes, complications appear. The most common etiologic agents are Neisseria gonorrhoeae, Chlamydia trachomatis, Treponema pallidum and Herpes simplex. In order to avoid dissemination and complications, laboratory tests are essential for diagnosis and proper therapy. The objective of this article was to raise awareness to sexually transmitted diseases in proctitis etiology, as well as their diagnosis and treatment.